Religiousness and health-related quality of life of older adults - Abdala, Gina Andrade; Kimura, Miako; Duarte, Yeda Aparecida de Oliveira; Lebrão, Maria Lúcia; Santos, Bernardo dos (Revista de Saúde Pública, 2015)
OBJECTIVE To examine whether religiousness mediates the relationship between sociodemographic factors, multimorbidity and health-related quality of life of older adults.METHODS This population-based cross-sectional study is part of the Survey on Health, Well-Being, and Aging (SABE). The sample was composed by 911 older adults from Sao Paulo, SP, Southeastern Brazil. Structural equation modeling was performed to assess the mediator effect of religiousness on the relationship between selected variables and health-related quality of life of older adults, with models for men and women. The independent variables were: age, education, family functioning and multimorbidity. The outcome variable was health-related quality of life of older adults, measured by SF-12 (physical and mental components). The mediator variables were organizational, non-organizational and intrinsic religiousness. Cronbach’s alpha values were: physical component = 0.85; mental component = 0.80; intrinsic religiousness = 0.89 and family APGAR (Adaptability, Partnership, Growth, Affection, and Resolve) = 0.91.RESULTS Higher levels of organizational and intrinsic religiousness were associated with better physical and mental components. Higher education, better family functioning and fewer diseases contributed directly to improved performance in physical and mental components, regardless of religiousness. For women, organizational religiousness mediated the relationship between age and physical (β = 2.401, p < 0.01) and mental (β = 1.663, p < 0.01) components. For men, intrinsic religiousness mediated the relationship between education and mental component (β = 7.158, p < 0.01).CONCLUSIONS Organizational and intrinsic religiousness had a beneficial effect on the relationship between age, education and health-related quality of life of these older adults.